Revising the Superorganism: An Organizational Approach to Complex Eusociality - Canciani, Mark; Arnellos, Argyris; Moreno, Alvaro (Frontiers in Psychology, 2019)
Eusociality is broadly defined as: colonies consisting of overlapping generations, cooperative brood care, and a reproductive division of labour where sterile (or non-reproductive) workers help the reproductive members. Colonies of many complex eusocial insect species (e.g. ants, bees, termites) exhibit traits, at the collective level, that are more analogous to biological individuals rather than to groups. Indeed, due to this, colonies of the most complex species are typically a unit of selection, which has led many authors to once again apply the concept of the superorganism to eusocial insects. However, unlike W. M. Wheeler, who originally employed the concept from a physiological and evolutionary perspective, today the superorganism is typically understood only from an evolutionary perspective, using group selection. This is because of the widely held view that eusocial colonies are self-organized systems. According to this view, even the most complex eusocial systems can be explained by appealing to a set of local interactions between parts of an initially disordered system (i.e. self-organization), without the need of any hierarchical control. In this paper we challenge the presupposition that hierarchical control and regulation is not possible in complex eusocial colonies. Using a case study of honey bees (Apis mellifera), we develop an alternative to the self-organization approach, that focuses on the hierarchical nature of the organization of complex eusocial systems—that we refer to as the hierarchical-organizational approach. In addition, we will analyse how colonies of eusocial insects show a complex set of interactions between the different organisms that bring forth a new cohesive collective organization, and how in turn the constitutive entities of this collective organization are transformed in this process. This paper argues that an inter-identity (namely the superorganism) emerges at the collective level in complex eusocial colonies, such as honey bees, due to the hierarchically-organized network of interactions within the colony.